Interest And Performance of Grade 10 Students in Science Modular Learning - Laguindab, Mamdoh; Basher, Salamah (International Journal of Science Education and Teaching, 2024)
This study aimed to investigate the students’ performance in science caused by their interest in science and their demographic profile indicated by sex, parents’ highest educational attainment, family income, and availability of gadget in a modular learning setting. An interest survey questionnaire which was developed and validated by the researcher and a demographic profile survey were administered to 122 grade 10 students of RPMD National Science High School, Marawi City, Philippines in the first month of the school year 2021-2022. The students were exposed to offline modular learning throughout the school year. The average final grade of the students at the end of the school year served as their performance in science. To support the quantitative data, in-depth interviews were conducted after the final grades became available. The quantitative data were treated and analyzed using descriptive statistics, Pearson correlation coefficient, Chi-square test, and Gamma test while the qualitative data were analyzed thematically. The findings of the study revealed that the interest in science was significantly related to performance in science (r=.522, p<.05, two tailed test). It also revealed that the sex was significantly associated with the interest in science (χ^2=7.149, p<.05, df=2) and the performance in science (χ^2=8.57, p<.05, df=2) in favor of girls. However, parents’ highest educational attainment, family income and availability of gadgets were not associated significantly with both interest and performance in science. Meanwhile, the qualitative data revealed that the higher the interest in science of the students, the greater the efforts they exerted in studying the modules and the higher the performance obtained. The study’s limitations include a small sample size, the lack of significant associations with parents’ education and family income, and its focus on offline modular learning, which may not apply to other educational contexts. Additionally, the timing of interviews after performance assessments may have limited insights into how students’ interest developed. Practical implications suggest the need for more engaging teaching strategies, gender-responsive policies, professional development for modular learning, and further research to explore other factors influencing science performance.